Address on Archaeology (Proceedings of the Society of Antiquaries of Scotland, 1862)
Professor J Y Simpson’s postponed Inaugural Address from the beginning of the session is printed in its entirety. He emphasises the variety of fields of study that involve archaeology, the increasingly scientific approach to the study of the past, and some of the conclusions reached by archaeologists in the past century. Professor Simpson then goes on to acknowledge the work of members of the Society in chronicling Scotland’s past but speculates about what information could be gained if antiquarians were able to converse with the spirits of ancient Scots, highlighting that there are many further lines of archaeological study to pursue. He also comments on the importance of both the excavation of artefacts and the study of written sources about Scotland’s past. To conclude his talk, he encourages his audience to advocate for the protection of historical monuments. Meeting notes for 10 December, 1860 are appended.